2023
DOI: 10.3390/medicines10070043
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Tumor-Specificity and Neurotoxicity between 3-Styrylchromones and Anti-Cancer Drugs

Abstract: Background. Many anti-cancer drugs used in clinical practice cause adverse events such as oral mucositis, neurotoxicity, and extravascular leakage. We have reported that two 3-styrylchromone derivatives, 7-methoxy-3-[(1E)-2-phenylethenyl]-4H-1-benzopyran-4-one (Compound A) and 3-[(1E)-2-(4-hydroxyphenyl)ethenyl]-7-methoxy-4H-1-benzopyran-4-one (Compound B), showed the highest tumor-specificity against human oral squamous cell carcinoma (OSCC) cell lines among 291 related compounds. After confirming their super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We have recently reported that two 3-styrylchromone derivatives, 7-methoxy-3-[(1 E )-2-phenylethenyl]-4 H -1-benzopyran-4-one (Compound A) and 3-[(1 E )-2-(4-hydroxyphenyl) ethenyl]-7-methoxy-4 H -1-benzopyran-4-one (Compound B), showed comparable TS values against human OSCC cell lines with 5-FU, cisplatin and doxorubicin. Quantitative structure-activity relationship (QSAR) prediction based on the Tox21 (21st century toxicology program) database suggested that compounds A and B may inhibit the signalling pathway of estrogen-related receptor α (ERRα), but not the other 58 signalling pathways ( Abe et al, 2023 ). Thus, it is urgent to test the possibility that selective inhibition of ERRα may also be involved in the anticancer activity of kaempferol ( 11 ) and withanolide D ( 18 ), and related compounds.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that two 3-styrylchromone derivatives, 7-methoxy-3-[(1 E )-2-phenylethenyl]-4 H -1-benzopyran-4-one (Compound A) and 3-[(1 E )-2-(4-hydroxyphenyl) ethenyl]-7-methoxy-4 H -1-benzopyran-4-one (Compound B), showed comparable TS values against human OSCC cell lines with 5-FU, cisplatin and doxorubicin. Quantitative structure-activity relationship (QSAR) prediction based on the Tox21 (21st century toxicology program) database suggested that compounds A and B may inhibit the signalling pathway of estrogen-related receptor α (ERRα), but not the other 58 signalling pathways ( Abe et al, 2023 ). Thus, it is urgent to test the possibility that selective inhibition of ERRα may also be involved in the anticancer activity of kaempferol ( 11 ) and withanolide D ( 18 ), and related compounds.…”
Section: Discussionmentioning
confidence: 99%